Peramalan nilai tukar rupiah terhadap dollar Amerika menggunakan model ARIMA - Wijaya, Andreas Rony (Majalah Ilmiah Matematika dan Statistika, 2023)
The exchange rate of the Rupiah against the currencies of other countries is one of the factors in identifying the condition of an economic condition. The value exchange rate can be strengthened or weakened at any time, according to the country's situation. Fluctuations of the Rupiah exchange rate could affect domestic inflation. Therefore, it is necessary to plan a good policy, considering the Rupiah's movement in the future. One of the currencies that affect the world's economic conditions is the United States Dollar. This study forecasts the Rupiah's exchange rate against the United States Dollar (USD). Data is obtained from Bank Indonesia, with the period of the data used from January 2018 to August 2022. One method of forecasting time series data is the Autoregressive Moving Average (ARIMA) method. The best model is selected based on the smallest AIC and BIC values. Based on the analysis of model selection, the ARIMA(1, 0, 1) model is the best model for forecasting the exchange rate of the Rupiah against the US Dollar. The results of the prediction of the Rupiah exchange rate show that the exchange rate of the Rupiah against the US Dollar has increased and decreased, which was not significant. Keywords: ARIMA, exchange rate, forecasting, time seriesMSC2020: 62M10